2019
DOI: 10.1038/s41467-019-10605-2
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of tidal triggering of earthquakes at mid-ocean ridges

Abstract: The strong tidal triggering of mid-ocean ridge earthquakes has remained unexplained because the earthquakes occur preferentially during low tide, when normal faulting earthquakes should be inhibited. Using Axial Volcano on the Juan de Fuca ridge as an example, we show that the axial magma chamber inflates/deflates in response to tidal stresses, producing Coulomb stresses on the faults that are opposite in sign to those produced by the tides. When the magma chamber’s bulk modulus is sufficiently low, the phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 58 publications
6
71
0
Order By: Relevance
“…Remarkably, Yabe et al (2015) and Scholz et al (2019) successfully applied equation 8 in good agreement with data without explicit theoretical underpinnings. While Yabe et al (2015) correctly state that R 0 is a reference rate when tidal stress is zero, the latter study refers to R as "the instantaneous seismicity rate".…”
Section: Discussionmentioning
confidence: 77%
“…Remarkably, Yabe et al (2015) and Scholz et al (2019) successfully applied equation 8 in good agreement with data without explicit theoretical underpinnings. While Yabe et al (2015) correctly state that R 0 is a reference rate when tidal stress is zero, the latter study refers to R as "the instantaneous seismicity rate".…”
Section: Discussionmentioning
confidence: 77%
“…Our experimental results suggest that if this patch is subjected to fluid pressure oscillations, local variations of slip rate could change the rate-and-state parameters and increase the critical stiffness, allowing for possible seismic slip. Such acceleration of the slip rate can have many fluid-related origins such as oceanic and earth tides (e.g., Houston, 2015;Rubinstein et al, 2008;Rydelek et al, 1992;Scholz et al, 2019), seasonal hydrology (e.g., Bettinelli et al, 2008;Chanard et al, 2014), or fluid production/injection into georeservoir (e.g., Candela et al, 2019;Verdon et al, 2013). In the case of fluid injection, it has been recently suggested that cyclic fluid injections would trigger less seismicity compared to traditional monotonic injections (e.g., Yoon et al, 2014;Zang et al, 2018Zang et al, , 2013.…”
Section: 1029/2019jb018517mentioning
confidence: 99%
“…Additionally, seismicity rate prior to the eruption was strongly correlated with tides, exhibiting the highest rates when ocean loading was at a minimum (Wilcock et al, 2016). Although it is likely that the effective strength of volcanic faults would respond to tidal stressing (Scholz et al, 2019;Tan et al, 2019), we do not resolve significant changes in Δσ with tidal stress ( Figure S9).…”
Section: Discussionmentioning
confidence: 87%